Novel aspects of preoperative chemoradiation therapy improving anti‐tumor immunity in pancreatic cancer. Issue 5 (31st March 2013) - Tsuchikawa, Takahiro; Hirano, Satoshi; Tanaka, Eiichi; Matsumoto, Joe; Kato, Kentaro; Nakamura, Toru; Ebihara, Yuma; Shichinohe, Toshiaki
<x xml:space="preserve">Abstract</x> Pancreatic cancer is an aggressive cancer with poor prognosis. Little is known about the immune response in the tumor microenvironment after chemotherapy for initially unresectable tumor. The purpose of this study was to investigate the immunological effects of chemoradiation therapy in the tumor microenvironment of pancreatic adenocarcinoma. Seventeen patients with pancreatic adenocarcinoma with and without preoperative chemoradiation therapy were retrospectively analyzed using immunohistochemical methods for HLA class I heavy chain, CD4+, CD8+, CD45RO+ and Foxp3+ T cell infiltrations. Seven of the 17 study patients received preoperative chemoradiation therapy. There were no statistically significant differences in the number of CD4+ and CD8+ T cell infiltrations in the tumor microenvironment. However, the number of Foxp3+ T cell infiltrations was significantly lower in the neoadjuvant chemoradiation therapy group. The HLA class I expression status was the same between the two groups. In conclusion, preoperative chemoradiation therapy in pancreatic adenocarcinoma is useful for reducing regulatory T cell levels in combination with its direct cytotoxic effects.